Inclusive institutions, unequal outcomes: Democracy, state capacity, and income inequality - Bahamonde Hector; Trasberg Mart (Elsevier, 2025)
Although the relationship between democratic rule and income inequality has received important attention in recent literature, the evidence has been far from conclusive. In this paper, we explore whether the redistributive effect of democratic rule is conditional on state capacity. Previous literature has outlined that pre-existing state capacity may be necessary for inequality-reducing policies under democratic rule. In contrast to that intuitive view, this study argues that democratic rule and high state capacity combined produce higher levels of income inequality over time. This relationship operates through the positive effect of high-capacity democratic context on foreign direct investment and financial development. By making use of a novel measure of state capacity based on cumulative census administration, we find empirical support for these claims using fixed-effects panel regressions with the data from 126 industrial and developing countries between 1970 and 2013.